PREDICTION OF DEVELOPMENT DIRECTION IN KENDARI CITY BASED ON CHANGES IN DENSITY OF BUILT-UP AREA - Jamal Harimudin; Fitriani Fitriani (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2020)
This research was conducted to determine changes in the area of built land and the direction of development of the city of Kendari in 2039 by using Landsat imagery at different times in Kendari City in 1999, 2009, and 2019. The method used is digital interpretation technique using NDBI algorithm (Normalized Difference Built-Up Index) to obtain building density information. Overlay analysis is used to determine changes in the density of built land over the past 20 years and Cellular Automata analysis to predict the density of built up land in the next 20 years. Testing the accuracy of the sample utilizes the confusion matrix on the actual constructed land density information in 2019. The results obtained in the form of information on the developed land density and its changes in 1999, 2009, and 2019 as well as information on the direction of development of the city of Kendari in the next 30 years. The analysis shows that in the period 1999 to 2009 there was a change of 2,206.09 Ha or as much as 8.17%. Then in the period 2009 to 2019 there was a change of 4,024.25 Ha or 14.90% of the total area of the study. There is a tendency for Kendari City to develop towards Baruga Districts and Puwatu Districts for the next 20 years.